2017
DOI: 10.1093/cvr/cvx095
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-specific loss of mitochondrial p32/C1qbp causes cardiomyopathy and activates stress responses

Abstract: These findings support a key role for mitochondrial p32 protein in cardiac myocytes modulating mitochondrial translation and function, and thereby survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 39 publications
2
54
0
Order By: Relevance
“…One top-scoring YBEY partner was the putative RNA-binding protein p32/C1QBP, critically required for mitochondrial metabolism and associated with a variety of mitochondrial diseases and cancer (67)(68)(69)(70)(71)(72)(73)(74)(75)(76). The interaction between the two proteins was confirmed in cross-pulldown assays with the alternate use of YBEY-3×FLAG and p32-HA proteins as bait and prey (Supplementary Figure 8A).…”
Section: Ybey Interacts With P32 and A Distinct Set Of Mitoribosomal mentioning
confidence: 86%
“…One top-scoring YBEY partner was the putative RNA-binding protein p32/C1QBP, critically required for mitochondrial metabolism and associated with a variety of mitochondrial diseases and cancer (67)(68)(69)(70)(71)(72)(73)(74)(75)(76). The interaction between the two proteins was confirmed in cross-pulldown assays with the alternate use of YBEY-3×FLAG and p32-HA proteins as bait and prey (Supplementary Figure 8A).…”
Section: Ybey Interacts With P32 and A Distinct Set Of Mitoribosomal mentioning
confidence: 86%
“…In summary, our study has identified the mitochondrial protein p32 as an important factor for metabolism and maturation in DCs. Recent studies on mice revealed that p32 is involved in cardiomyopathy (Saito et al, 2017), innate immunity (Sasaki et al, 2017), and obesity (Liu et al, 2017). Moreover, p32 mutations are associated with a clinical spectrum ranging from infantile lactic acidosis to childhood cardiomyopathy and late-onset progressive external ophthalmoplegia in humans (Feichtinger et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using macrophages and mouse embryonic fibroblasts (MEFs), we demonstrated that p32 is required for appropriate interleukin (IL)-6 production upon lipopolysaccharide (LPS) stimulation (Sasaki et al, 2017). Recent studies showed that p32 mutations impair the mitochondrial respiratory chain and cause cardiomyopathy in humans and mice (Feichtinger et al, 2017;Saito et al, 2017). However, despite the importance of mitochondrial functions, the exact mechanisms of p32 functions in DCs remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry was conducted as described previously [18] with anti-von Willebrand Factor antibody (#65707; Cell Signaling Technology, Beverly, MA, U.S.A.).…”
Section: Immunohistochemistrymentioning
confidence: 99%